Spermidine alleviates thymopoiesis defects and aging of the peripheral T-cell population in mice after radiation exposure - Kengo Yoshida; Zhenqiu Liu; Yoshiko Kubo; Masahiko Miura; Mika Yamaoka; Hiroko Nagamura; Munechika Misumi; Yoichiro Kusunoki (Experimental Gerontology)
The T cell aging process can be modified by genotoxic factors, including ionizing radiation, and metabolic controls, such as caloric restriction; the former accelerates and the latter retards the process. However, the mechanisms by which these systemic factors interact to cause T cell aging remain unclear. This study investigated the naïve T-cell pool, thymic cellularity, and transcriptome in mice irradiated with 3.8 Gy at 5 weeks of age and treated 13 months later with 30 mM spermidine (SPD), a metabolism regulator. The number of conventional naïve CD4 and CD8 T cells in the peripheral blood decreased 14 months after irradiation whereas the number of virtual memory naïve T cells, which increased with age, further increased by irradiation. However, these radiation-related changes were not significant in similarly irradiated mice that were subsequently treated with SPD. The numbers of total, double-positive, and single-positive thymocytes were decreased by irradiation, whereas none were decreased in the irradiated mice treated with SPD. RNA sequencing of thymus cells revealed 803 upregulated genes in irradiated mice compared with those in non-irradiated control mice, with these genes enriched in leukocyte activation and inflammatory cytokine production. However, only 22 genes were upregulated in irradiated and SPD-treated mice, suggesting a reversal of many radiation-induced gene expression changes. These findings suggest that SPD may alleviate radiation-induced acceleration of T-cell aging, particularly by mitigating reduced thymopoiesis and inflammation. Further research is warranted to explore the rejuvenating potential of SPD and its mechanisms of action in accelerated T-cell aging.